The role of artificial intelligence in social media: Implications for digital earnings and the future of online economies - Hussnain, Ali; Nadeem, Zakra (Journal of Sustainable Community Development, 2025)
Integrating Artificial Intelligence (AI) within social media platforms has fundamentally transformed digital communication, content distribution, and monetisation strategies. This research article explores how AI technologies are revolutionizing social media, influencing user engagement, advertising strategies, and the earnings of digital content creators. Through an extensive literature review and critical analysis of recent case studies, the study discusses AI-driven personalization, recommendation systems, and predictive analytics that enable more targeted advertising and efficient revenue generation. The findings illustrate that while AI significantly enhances monetisation potential, it raises ethical and regulatory challenges regarding privacy, algorithmic bias, and transparency. Finally, recommendations for policymakers, social media companies, and content creators are proposed to foster sustainable economic models in an increasingly AI-driven digital ecosystem.